Ultrahigh-Porosity MgO Microparticles for Heat-Energy Storage - Kim, Youngho; Dong, Xue; Chae, Sudong; Asghar, Ghulam; Choi, Sungwoong; Kim, Bum Jun; Choi, Jae Young; Yu, Hak Ki (Advanced Materials, 2023)
Continuous industrial development has increased the demand of energy. Inevitably, the development of energy sources is steadily progressing using various methods. Rather than establishing a new energy source, a system for storing waste heat generated by industry has now been accepted as a useful strategy. Among such systems, the hydration and dehydration reactions of MgO/Mg(OH)2 are eco-friendly, have relatively low toxicity and risk, and have a large reserves. Therefore, it is a promising candidate for a heat-storage system. In this study, ultrahigh-porosity particles are used to maximize the heat-storage efficiency of pure MgO. Due to its large surface area, the heat storage rate is 90.3% of the theoretical value and the reaction rate is very high. In addition, as structural collapse, likely to be caused by volume changes between reactions, is blocked as the porous region is filled and emptied, the cycle stability is secured. Ultrahigh-porosity MgO microparticles can be used to build eco-friendly heat-storage systems.
Keywords: Buffering volume expansion; Eco-friendly; Extensive specific surface area; Heat energy storage; Heat storage systems; Hydration reaction; Industrial development; Micro particles; Ultrahigh-porosity MgO; Volume expansion; buffering volume expansion; extensive specific surface areas; heat-storage systems; hydration reactions; ultrahigh-porosity MgO